Sosialisasi Bahaya Penyalahgunaan Narkoba dalam Upaya Membangun Generasi Sehat di Desa Lumban Gurning - Dwison S. Dachi; Gracia P.D.Br. Simangunsong; Febrianto Pakpahan; Ferdinan D. Sihotang; Felix E. Barus; Eben Oktavianus Zai (Lembaga Pengembangan Kinerja Dosen, 2025)
Drug abuse in today's young generation is one of the serious problems that has a very negative and very bad effect on the physical, social and future health of today's young generation. The purpose of the activity of socialization of the dangers of drug abuse for the young generation in Lumban Gurning Village is so that the young generation in Lumban Gurning Village can increase awareness and knowledge, and prevent drug abuse, and can build a healthy young generation and create a healthy environment. Drug abuse is one of the very serious problems in Indonesia, especially in the young generation. The method used in this socialization is the lecture and discussion method. In this socialization activity, the level of knowledge of people about drugs and the dangers of drugs has been quite good, but in their efforts to understand the prevention of drug abuse is still not good. Therefore, it is necessary to carry out socialization by trying to inform it maximally, especially in terms of strengthening topics and news about more effective ways of preventing the dangers of drugs, by carrying out socialization about drug abuse, it can help the people of Lumban Gurning Village to be more careful and understand more about what drugs really are. By understanding what drugs are, the community in Lumban Gurning village can prevent and overcome drug abuse.